Figure of Speech Use in the Song Lyrics of Jhon Legend album "Bigger Love" - Desak Putu Eka Pratiwi; I Gusti Ayu Vina Widiadnya Putri; Yohanes Kapistrano Agung (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
The aim of this study is to find out the types of figure of speech used in the song lyric of John Legend album Bigger Love. The data were analyzed by using the theory proposed by Knickerbocker and Rreninger (1963). In analyzing the data, this study uses observation method in collecting the data and descriptive method uses in analyzing the data. The result of this study showed that six types of figure of speech used in the song lyric of John Legend album Bigger Love, that there were 22 data the figure of speech used in the song lyric of John Legend album Bigger Love, those are 8 simile, 2 metaphor, 3 personification, 1 synecdoche, 6 hyperbole, 1 paradox.